OPTIMALISASI PEMANFAATAN TEKNOLOGI DALAM STRATEGI PROMOSI DI MI NURUL HIKMAH - Rahman, Muh Suryadi Triputra; Mappalotteng, Abd. Muis; Abdul Wahid (Global Action and Education for Society, 2025)
This research is a type of development research aimed at: (1) producing a learning module for the subject of Network System Administration for the XI grade of Computer and Network Engineering at SMK Negeri 4 Gowa; (2) determining the validity of the interactive learning module for the subject of Network System Administration for the XI grade of Computer and Network Engineering at SMK Negeri 4 Gowa. This research uses the ADDIE development model, which consists of five stages: (1) Analysis; (2) Design; (3) Development; (4) Implementation, conducted through small group trials with 15 subjects and large group trials with 31 subjects; and (5) Evaluation. This development resulted in a learning module that includes several interactive elements, such as practical videos, interactive quizzes, and Augmented Reality. The developed learning module was declared valid by the media and material expert team with very valid criteria. Based on trials with small groups, large groups, and teacher responses, the developed module is also declared valid and falls into the very valid category. Thus, the evaluation results of this module development indicate that this learning module is valid for use in the teaching and learning process of XI grade Computer and Network Engineering students at SMK Negeri 4 Gowa.